Bacteriological profile and antimicrobial susceptibility patterns of diabetic foot ulcers: a prospective cross-sectional study. (Student's Journal of Health Research Africa, 2026)
BackgroundDiabetic foot ulcers are a major source of infection-related morbidity, prolonged hospitalisation and lower-limb amputation. Their microbial spectrum varies across settings, while antimicrobial resistance increasingly limits empirical treatment.ObjectivesTo characterise the bacteriological profile of clinically infected diabetic foot ulcers and determine the antimicrobial susceptibility patterns of recovered bacterial isolates in a tertiary-care hospital.MethodsThis prospective cross-sectional study included 71 adults with type 2 diabetes and clinically infected foot ulcers presenting from January to December 2024. Deep wound swabs, aspirated pus or tissue specimens were collected after wound preparation and processed by conventional culture and biochemical methods. Antimicrobial susceptibility was assessed by Kirby-Bauer disk diffusion using contemporaneous Clinical and Laboratory Standards Institute criteria. Multidrug resistance was defined as non-susceptibility to at least one agent in three or more antimicrobial categories.ResultsSignificant bacterial growth was obtained from 62 of 71 specimens (87.3%). Staphylococcus aureus was the most frequent isolate (24.2%), followed by Escherichia coli (17.7%), Proteus species (16.1%) and Pseudomonas aeruginosa (12.9%). Polymicrobial infection occurred in 21.0% of culture-positive cases. Five of 15 S. aureus isolates (33.3%) were methicillin resistant. Resistance among E. coli was highest to amoxicillin-clavulanate (72.7%) and cotrimoxazole (54.5%), whereas meropenem and levofloxacin showed comparatively lower resistance (27.3% each). Overall, 19 isolates (30.6%) met the multidrug-resistance definition.ConclusionClinically infected diabetic foot ulcers in this setting contained mixed bacterial flora with a substantial antimicrobial-resistance burden. Culture-directed therapy should accompany timely debridement, glycaemic optimisation and structured wound care.RecommendationsLocal antibiograms should be updated periodically, and empirical regimens should be reviewed promptly after culture results become available.
Keywords: antimicrobial resistance; bacterial culture; diabetic foot infection; diabetic foot ulcer; multidrug resistance; Staphylococcus aureus